Placental lipoprotein lipase DNA methylation levels are associated with gestational diabetes mellitus and maternal and cord blood lipid profiles. (12th February 2014) - Houde, A. A.; St-Pierre, J.; Hivert, M. F.; Baillargeon, J. P.; Perron, P.; Gaudet, D.; Brisson, D.; Bouchard, L.
Abstract : Placental lipoprotein lipase (LPL) is crucial for placental lipid transfer. Impaired LPL gene expression and activity were reported in pregnancies complicated by gestational diabetes mellitus (GDM) and intra-uterine growth restriction. We hypothesized that placental LPL DNA methylation is altered by maternal metabolic status and could contribute to fetal programming. The objective of this study was thus to assess whether placental LPL DNA methylation is associated with GDM and both maternal and newborn lipid profiles. Placenta biopsies were sampled at delivery from 126 women including 27 women with GDM diagnosed following a post 75 g-oral glucose tolerance test (OGTT) between weeks 24 and 28 of gestation. Placental LPL DNA methylation and expression levels were determined using bisulfite pyrosequencing and quantitative real-time PCR, respectively. DNA methylation levels within LPL proximal promoter region (CpG1) and intron 1 CpG island (CpGs 2 and 3) were lower in placenta of women with GDM. DNA methylation levels at LPL -CpG1 and CpG3 were also negatively correlated with maternal glucose (2-h post OGTT; r =–0.22; P =0.02) and HDL-cholesterol levels (third trimester of pregnancy; r =–0.20; p =0.03), respectively. Moreover, we report correlation between LPL -CpG2 DNA methylation and cord blood lipid profile. DNA methylation levels within intron 1 CpG island explained up to 26% ( r ⩽–0.51; P <0.001) of placental LPL mRNA expression variance. Overall, we showed that maternal metabolic profile is associated with placental LPL DNA methylation dysregulation. Our results suggest that site-specific LPL epipolymorphisms in the placenta are possibly functional and could potentially be involved in determining the future metabolic health of the newborn.